Reducing Inhomogeneous Current Density Distribution in Graphite Electrodes by Design Variation. Issue 11 (1st January 2017) - Kindermann, Frank M.; Osswald, Patrick J.; Ehlert, Günter; Schuster, Jörg; Rheinfeld, Alexander; Jossen, Andreas
Abstract : Inhomogeneous utilization of electrodes and consequent limitations in the operating conditions are a severe problem, reducing lifetime and safety. By using a previously developed laboratory cell setup, we are able to show an inhomogeneous retrieval of lithium-ions from a graphite electrode throughout the layer with spatial resolution for two different graphites. After provoking inhomogeneities via constant current operations, equilibration processes are recorded and are assigned to two different effects. One effect is an equilibration inside the particles (intra-particle) from surface to bulk whereas the second effect is an equalization between the particles (inter-particle) to reach a homogeneous degree of lithiation in each particle throughout the electrode layer. With the recorded data, we implemented a P2D model with multiple particle sizes and considered the electrode thickness in several separate domains. Using the relaxation data of intra- and inter-particle relaxation for parametrizing the model, we investigated the influence of different solid and liquid phase parameters. As the liquid phase parameters scaled via porosity and tortuosity showed the biggest impact, we performed a design variation study to achieve a more homogeneous utilization of the electrode. Structuring the electrode to lower tortuosity is identified as the most promising design variation for homogeneous utilization.